Comparative study of accounting for deferred tax, foreign exchange and goodwill in Australia, UK, US and Singapore - Koh, Siew Huay (2014)
Accounting treatment for deferred tax, foreign exchange and goodwill have always been confusing and subjected to much debate over the years among the countries. Difference in standards and practices among the countries in these areas have further complicated the issues of deferred tax, foreign exchange and goodwill. As a result, the purpose of this report is to compare the difference views undertaking by the accounting bodies of Australia, Singapore, UK. and US. on these issues.